Implementation Of The Complete Systematic Land Registration Program (Ptsl) As An Effort To Accelerate Land Registration In Pagadungan Village, Tempuran District, Karawang Regency - Rahadian, Rian; Sudjadi, Agung; Abdurakhman, Maman; Putri, Afifah Nuranti; Andriani , Nina; Ramadhan, Mochmad Andhika; Kalimanto, Miki (Jurnal Hukum dan Keadilan, 2024)
Pagadungan Village, Karawang Regency as the object of research. Pagadungan Village is one of the villages that has carried out the Complete Systematic Registration Program (PTSL) which is being echoed by the ATR / BPN ministry from 2018 to 2023 as the Main Objective of Agrarian Reform. This research is qualitative in nature, namely making direct observations to Pagadungan Village and studying qualitatively, namely collecting information obtained from perceptions and inspection reports outlined in the journal. The results obtained show that the Complete Systematic Registration Program (PTSL) in Pagadungan Village, Karawang Regency had reached 1700 registered lands from the target of 1900.  This means that the Complete Systematic Registration Program (PTSL) in Pagadungan Village has reached 90% of the Target, thus exceeding the achievement of the national target of 72% of the National Target. Because the Complete Systematic Land Registration Program is one of the Efforts to Accelerate Land Registration in order to Achieve Economic added Value and Legal Certainty. This research can be concluded that Pagadungan Village is successful in implementing the Complete Systematic Registration Program (PTSL).  The success in implementing the Complete Systematic Registration Program (PTSL) can make a positive contribution to the community's economy in creating social welfare.